Strategi Peningkatan Pendapatan Asli Daerah (PAD) Melalui Investasi Daerah Kota Palu - Saleh, Ismail; Burhanuddin, Burhanuddin; Nursiah, Nursiah; Mande, Henni (Tangible Journal, 2025)
This study aims to analyze strategies for increasing Local Own Revenue (PAD) through regional investment in Palu City. The research method used is descriptive qualitative with a case study approach. Data were collected through documentation studies, in-depth interviews with key informants from BPKAD, DPMPTSP, Bappeda Palu City, and field observations. The results showed that Palu City's PAD has fluctuated over the past 10 years with the largest contribution from local taxes and levies. Regional investment through regional-owned enterprises (BUMD) has not been optimal in providing significant contribution to PAD. PAD enhancement strategies include: (1) optimizing regional asset management, (2) developing profitable BUMDs, (3) increasing investment in potential sectors, and (4) improving regional investment governance. This research provides policy recommendations to increase the effectiveness of regional investment as a sustainable source of PAD.